2022
DOI: 10.1073/pnas.2205356119
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and financial coping strategies among energy-insecure households

Abstract: When households struggle to pay their energy bills and avoid being disconnected from the grid, they may accrue debt, forgo expenses on food, and use space heaters or ovens to warm their homes. These coping strategies can introduce significant physical and financial risks. In this study, we analyze an original survey with a representative sample of low-income households during the first year of the COVID-19 pandemic, from June 2020 to May 2021. We evaluate the prevalence of a wide range of coping strategies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Evidence shows that when attempting to avoid utility disconnection, households often engage in a set of economically harmful coping strategies, such as accruing credit card debt or strategically skipping bill payments. 22 In this context, our findings suggest that disconnection moratoria have an economic impact beyond utility service shutoffs by allowing families to avoid tradeoffs between keeping the power on and carrying debt, having enough to eat, or seeking medical assistance.…”
Section: Discussionmentioning
confidence: 81%
“…Evidence shows that when attempting to avoid utility disconnection, households often engage in a set of economically harmful coping strategies, such as accruing credit card debt or strategically skipping bill payments. 22 In this context, our findings suggest that disconnection moratoria have an economic impact beyond utility service shutoffs by allowing families to avoid tradeoffs between keeping the power on and carrying debt, having enough to eat, or seeking medical assistance.…”
Section: Discussionmentioning
confidence: 81%
“…One category of policy response may be direct cash payments to help the federal government better target energy-related vulnerable populations so that energy assistance funds such as the Low-Income Home Energy Assistance Program and the Weatherization Assistance Program can be directed to the most affected and neediest populations. Particularly, for low-income people caught in the energy poverty trap, such assistance can reduce financial hardship and help them make specific upgrades [69]. Further guidance through energy audits and efficiency programs can provide suggestions and inkind support.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…This systematic literature review has identified that various terms are used to address similar aspects of energy inequality (see Figure 1) [17], including energy poverty [9,14,18,20,21,26,32,37], energy insecurity [17,38], fuel poverty [39][40][41][42][43], environmental inequality [34], carbon inequality [44], and environmental degradation [13,31,36]. To achieve the objective of this study, which is to identify energy inequality dimensions and their indicators and explore ways to reduce them, it is crucial to establish a common understanding and terminology.…”
Section: The Conceptmentioning
confidence: 99%
“…The lack of equitable access to energy and the financial burden it poses contribute to the complex dynamics of energy inequality and insecurity, necessitating attention and action within the framework of energy justice [17]. In the context of household, energy insecurity refers to a household's struggle to pay energy bills and exposure to inadequate residential energy services, which is a widespread problem across the world [38]. Households experiencing energy insecurity face challenging choices every day as they try to balance the need to keep their power on and maintain safe indoor temperatures, while also meeting other essential needs like food and healthcare.…”
Section: The Conceptmentioning
confidence: 99%